2014
DOI: 10.1007/s00253-014-6284-4
|View full text |Cite
|
Sign up to set email alerts
|

Engineering increased triacylglycerol accumulation in Saccharomyces cerevisiae using a modified type 1 plant diacylglycerol acyltransferase

Abstract: Diacylglycerol acyltransferase (DGAT) catalyzes the acyl-CoA-dependent acylation of sn-1,2-diacylglycerol to produce triacylglycerol (TAG). This enzyme, which is critical to numerous facets of oilseed development, has been highlighted as a genetic engineering target to increase storage lipid production in microorganisms designed for biofuel applications. Here, four transcriptionally active DGAT1 genes were identified and characterized from the oil crop Brassica napus. Overexpression of each BnaDGAT1 in Sacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 39 publications
(46 reference statements)
2
45
0
1
Order By: Relevance
“…DGAT has gained increasing interest in various organisms including algae, and its engineering potential for oil production in yeast and higher plants has been well documented [6266]. We here conducted the in-depth characterization of NoDGAT1A from N. oceanica , an oleaginous and industrially important marine alga.…”
Section: Discussionmentioning
confidence: 99%
“…DGAT has gained increasing interest in various organisms including algae, and its engineering potential for oil production in yeast and higher plants has been well documented [6266]. We here conducted the in-depth characterization of NoDGAT1A from N. oceanica , an oleaginous and industrially important marine alga.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that four homologous B. napus DGAT1 genes encode four isoforms of the enzyme (Aznar-Moreno et al, 2015;Greer et al, 2015), referred to as BnaA.DGAT1.a, BnaA. DGAT1.b, BnaC.DGAT1.a, and BnaC.DGAT1.b , with the main differences in amino acid sequence occurring in the IDR.…”
Section: The Motif Identified Is Composed Of [Hr][rk]x[krq][de]mentioning
confidence: 99%
“…The N and C termini of tung tree (Vernicia fordii) DGAT1 were both localized in the cytosol, and a C-terminal endoplasmic reticulum (ER) retrieval motif was shown to target the plant enzyme to the ER (Shockey et al, 2006). Recently, four highly homologous isoforms of B. napus DGAT1, recombinantly produced in Saccharomyces cerevisiae H1246, were partially characterized (Aznar-Moreno et al, 2015;Greer et al, 2015Greer et al, , 2016, and recombinant isoform BnaC.DGAT1.a was highly purified in active form (Caldo et al, 2015). A recombinant hydrophilic N-terminal fragment of isoform BnaA.DGAT1.b was shown previously to self-associate and interact with acyl-CoA through positive cooperativity based on the Lipidex-1000 assay (Weselake et al, 2006).…”
mentioning
confidence: 99%
“…Previous engineering efforts in S. cerevisiae showed a promising increase in lipid content by over-expressing a type 1 plant DGA (Greer et al, 2015). Total lipid production from glycerol was less than 12% dcw but represented nearly a doubling over empty vector control (Yu et al, 2013), and up to 17% dcw lipids, a four-fold increase by over-expression of FAS1, FAS2, and ACC1 with small amounts (up to 4 g/L) of ethanol being produced (Runguphan and Keasling, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Through the expression of the bacterial xylose isomerase (Karhumaa et The classical definition of an oleaginous yeast is one that accumulates greater than 20% dry cell weight (dcw) as lipids. S. cerevisiae is not known as being oleaginous and typically only accumulates 10-15% dcw lipids (Turcotte and Kosaric, 1989 Greer et al, 2015) whereas oleaginous yeasts typically accumulate 25% to greater than 60% dcw lipids (Ageitos et al, 2011). Recently engineering efforts to increase lipid content have been made in oleaginous yeasts and one target has been the protein kinase SNF1 gene.…”
Section: Introductionmentioning
confidence: 99%